VAPBr: Values in Digital Games for Public Service in Brazil - Tadeu Moreira de Classe (Serious Games Society, 2021)
In Brazil, many initiatives have emerged to promote the dialogue between citizens and public institutions using technology. This dialogue has been a challenging endeavor, and digital games have been proposed to stimulate interaction and understanding about public service process delivery. In this context, one fundamental aspect observed for the effectiveness of these games is the human values that the games can transmit. This paper proposes the “Values at Play Brazil” (VAPBr), a deck composed of 24 cards as a brainstorming tool to help designers identify values for public process-based digital games. The paper describes the design of VAPBr and its evaluation with 14 game designers aiming to obtain participants’ perception of VAPBr capability of clearly describing values and its usefulness for identifying them for a game. Results show a positive perception of VAPBr as a brainstorming tool to discover values to be designed in a public processbased digital game.